Living Donor Uterus Transplant and Surrogacy: Ethical Analysis According to the Principle of Equipoise. Issue 4 (18th November 2016) - Testa, G.; Koon, E. C.; Johannesson, L.
Abstract : The uterus is the most recent addition to the list of organs that can be successfully transplanted in humans. This article analyzes living donor uterus transplantation according to the ethical principle of equipoise. A comparison is made between living donor uterus transplantation and gestational surrogate motherhood. Both are solutions to absolute uterine infertility that allow the transfer of genetic material from intended parents to a child. The analysis concludes that living donor uterus transplantation does not violate the ethical principle of equipoise and should be considered an ethically acceptable solution to absolute uterine infertility. Abstract : This viewpoint of the ethics of living donor uterus transplantation and surrogacy under the principle of clinical equipoise suggests that living donor uterus transplantation is comparable, if not superior, to surrogacy from an ethical point of view.